FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS PADA PT. ASTRA OTOPARTS Tbk - Nasriah Akil (AkMen JURNAL ILMIAH, 2018)
The purpose of this research is to find out the comparison of liquidity and solvency of profitability in the company PT. Astra Otoparts Tbk. Quantitative research methodsused in this study, by collecting data based on the form of company financial public statements. Multiple linear regression using for analyzing research. The results show that the liquidity ratio has a positive effect on profitability, moreover the solvency ratio has a positive effect on profitability and there is a simultaneous influence between liquidity and solvency on profitability ratios. The conclusion of this research show there is a significant effect between liquidity ratios and profitability, and also solvency ratios with profitability, and liquidity ratios with solvability indicate a simultaneous effect on profitability ratios.